A genetic algorithm application using fuzzy processing times in non-identical parallel machine scheduling problem - Alcan, Pelin; Basligil, Huseyin (ELSEVIER SCI LTD, 2012)
There are many scheduling problems which are NP-hard in the literature. Several heuristics and dispatching rules are proposed to solve such hard combinatorial optimization problems. Genetic algorithms (GA) have shown great advantages in solving the combinatorial optimization problems in view of its characteristic that has high efficiency and that is fit for practical application [1]. Two different scale numerical examples demonstrate the genetic algorithm proposed is efficient and fit for larger scale identical parallel machine scheduling problem for minimizing the makespan. But, even though it is a common problem in the industry, only a small number of studies deal with non-identical parallel machines. In this article, a kind of genetic algorithm based on machine code for minimizing the processing times in non-identical machine scheduling problem is presented. Also triangular fuzzy processing times are used in order to adapt the GA to non-identical parallel machine scheduling problem in the paper. Fuzzy systems are excellent tools for representing heuristic, commonsense rules. That is why we try to use fuzzy systems in this study. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Job scheduling; Non-identical parallel machines; Heuristics; Fuzzy logic; Genetic algorithm (GA); Fuzzy processing times; MAKESPAN; Computer Science; Engineering